O mito nas Heróides de Ovídio: epístola I (De Penélope a Ulisses) - Oréfice, Patrícia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The objective of this work is to carry out a study about some aspects of the myth in the book Heroides, written by the Latin author Ovid (43 b.C. – 17/18 A.D.). To do so, this study will focus on the Letter I (“From Penelope to Ulysses”) approaching not only the stylistic issues of the elegiac genre, but also, studying them in connection with the epistolary subgenre. Departing from some biographical remarks about the author and from studies made by scholars about this poet, this work seeks to address the myth and certain little explored features of this genre, as the use of rhetoric

Este trabalho tem por objetivo realizar um estudo sobre aspectos do mito na obra Heróides, escrita pelo autor latino Ovídio (43 a.C. – 17/18 d.C.). Para tanto, este trabalho ocupar-se-á da Carta ou Epístola I (“De Penélope a Ulisses”), abordando não só questões estilísticas do gênero elegíaco, mas, também procurando identificar traços característicos das epístolas. Através de um mapeamento da biografia do autor e em estudos feitos por pesquisadores a respeito do poeta, procurou-se abordar o mito e certos recursos pouco explorados desse gênero, como o uso da retórica
Keywords: Ovídio - Heróides; Mitologia classica; Literatura classica; Literatura latina; Mito; Myth; Penelope; Ulysses